Perioperative management with phosphodiesterase type 5 inhibitor and prostaglandin E1 for moderate portopulmonary hypertension following adult-to-adult living-donor liver transplantation: a case report - Onoe, Takashi (Surg Case Rep, 2018)
BACKGROUND: Portopulmonary hypertension (PPH) is a relatively rare but well-recognized complication of end-stage liver disease. Moderate or severe PPH (mean pulmonary artery pressure [mPAP] ≥ 35 mmHg) is usually a contraindication for liver transplantation due to high operation-related mortality. Here, we report on a patient with moderate PPH whose condition was successfully managed with a phosphodiesterase type 5 (PDE5) inhibitor (tadalafil) and prostaglandin E1, who experienced rapid improvement of PPH after living-donor liver transplantation (LDLT). CASE PRESENTATION: A 63-year-old woman with alcoholic decompensated cirrhosis was referred to our hospital for LDLT. She had mild dyspnea on exertion as well as fatigue. Echocardiography and subsequent cardiac catheterization revealed a high mPAP (35 mmHg), and she was diagnosed with moderate PPH. We commenced treatment with oral tadalafil for the PPH. A second preoperative echocardiography demonstrated improved PPH, and she underwent LDLT. An intravenous infusion of prostaglandin E1 was introduced instead of tadalafil during and after the operation. The mPAP value showed a rapid decrease in mPAP value to 22 mmHg in 2 days. After discontinuation of the prostaglandin E1, the mPAP value remained 23 mmHg. Postoperative catheterization 2 months after LDLT showed no exacerbation of PPH. She was discharged on foot 70 days after LDLT in good condition and has shown a good clinical condition more than 2 years after LDLT. CONCLUSION: LDLT could be a radical treatment for PPH with careful management and adequate patient selection. PDE5 inhibitor and PGE1 is effective and feasible for perioperative management of the patient with moderate portopulmonary hypertension in LDLT.